9 months that made you [videorecording (DVD)] - Goritsas, Demetri (PBS, 2016)
Discover the thrilling story of how people are made, from the moment of conception to the moment of birth 280 days later. Follow the gestation process, the most exquisite biological choreography found in nature. Using the latest research and advances in medicine, we can reveal this hidden world in forensic detail. Zeroing in on milestones along the road to creation; where critical events can change people's life.